Is there a Middle East? the evolution of a geopolitical concept - Bonine, Michael E.; Amanat, Abbas; Gasper, Michael Ezekiel (Stanford University Press, 2012)
At a time when geopolitical forces, social currents, and environmental concerns have brought attention to the region, this volume examines the very definition and geographic and cultural boundaries of the Middle East in an unprecedented way.